2009
DOI: 10.1055/s-0030-1248249
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Early Severe Intraventricular Haemorrhage in Very Low Birth Weight Infants

Abstract: Birth weight and arterial hypotension were factors related to early IVH grade III, whereas hypercapnia and large BE were factors related to IVH grade IV in VLBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
5
15
0
Order By: Relevance
“…Regardless of IUGR, lower GA was an important predictor of NBAs, which was in line with the results of previous studies [13,21]. Considering that some neonates may not have IVH during the first days after birth, but after admission to the neonatal intensive care unit following postbirth events, such as respiratory problems and respiratory distress syndrome in particular, have been recognized as important risk factors in the development of germinal matrix hemorrhage-IVH [22,23], we wanted to examine the course of IVH in these infants over time, similar to Cruz-Martinez et al [13].…”
Section: Discussionsupporting
confidence: 89%
“…Regardless of IUGR, lower GA was an important predictor of NBAs, which was in line with the results of previous studies [13,21]. Considering that some neonates may not have IVH during the first days after birth, but after admission to the neonatal intensive care unit following postbirth events, such as respiratory problems and respiratory distress syndrome in particular, have been recognized as important risk factors in the development of germinal matrix hemorrhage-IVH [22,23], we wanted to examine the course of IVH in these infants over time, similar to Cruz-Martinez et al [13].…”
Section: Discussionsupporting
confidence: 89%
“…Despite the increasing survival rate of premature infants during recent decades, IVH is still one of the major causes of neurologic developmental problems (24)(25)(26). Inadequate functioning of autoregulation of cerebral blood flow has been considered as pathogenic factor in IVH (8).…”
Section: Discussionmentioning
confidence: 99%
“…In almost 90% cases, IVH occurs in the first 4 d of life (1). Several studies found an association between cardiovascular instability immediately after birth and IVH in VLBW infants (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Circulatory management in the neonatal intensive care unit (NICU) mainly focuses on elevation of blood pressure (6,7). Several studies have identified an association between hypotension and poor neurodevelopmental outcomes (1,3).…”
mentioning
confidence: 99%